Looking back, moving forward a review of group and team-based research - Neale, Margaret Ann; Mannix, Elizabeth A., 1960- (Research on managing groups and teams ;, 2012)
This volume is composed of a series of invited chapters from authors who are central and prolific contributors to the areas of group and team-based research. As such, each chapter provides an excellent overview of the current state of the research and a perspective on where scholars should be focusing their future research.